The development of medium-size airport-terminal interface simulation model - Wo, Sam Chong; Sharif, M. N.; Nakamura K.; Pakorn Adulbhan; Drew, Donald R.; Lee Foundation of Singapore (Bangkok : Asian Institute of Technology, 1972)
This study has approached the general problem of airport terminal passenger and baggage control by means of queueing theory and simulation. According to the passenger and baggage flow procedure in airport-terminal, a multichannel multistation queueing model for the control of passenger and baggage has been proposed and the simulation model was constructed. Two sub-systems were examined. One called the A-system, treats the arriving passenger process; the other system, called D-system, deals with the departing passenger process. The average and maximum queue length at various service facilities, the average and maximum waiting times for passenger to be serviced, the maximum queue of passenger at departure lounge and at baggage claim and customs area, the delays to the flight departure times, the total service time for the arrival process are figures of merit defined for identifying the projected situation for handling the passenger and baggage control. The arrival and departure process for the non-mixed flight situation under open- loop system assumption were analyzed. Regression analysis for determining an approximate relationship between the figures of merit and pertinent independent variables was performed by stepwise procedure. An arbitrary daily arrival and departure flight schedule was assumed and the mixed-flight situations were studied. The results indicate that a tolerable control of passenger and baggage flow can be achieved by utilizing our simulation model. In order to make the system more state-responsive through improvements in the management information control system, the state-dependent queueing model containing appropriate feed-back parameter is incorporated into our simulation model. The effective way of arranging servers for-various service facilities was also considered. Non-mixed and mixed-flight cases were again studied with additional considerations on stochastic process for arrival times and passenger input. Finally, an attempt to give a conceptual picture of the approach to the optimal decision-making was made. The Model for determining the optimum number of servers for arrival immigration and customs service, the optimum baggage flow rate, and the optimum decision rule on the number of check-in counters assigned for service have been established with the cost consideration.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1972
Keywords: Airports -- Mathematical models